Orlando eaudiobook A biography. - Woolf, Virginia (Recorded Books Inc., 2016)
Moving from one century into the next, oblivious to time and dimension, Orlando consorts with writers and monarchs, actors and gypsies, dropping one fashion and folly for another, and waking up at the end of a deep sleep, not only in a different age, but in a different gender. When it was published in 1928, Orlando's playful experimentation with the idea of androgyny was considered unique and vaguely scandalous. Today, the novel has come resoundingly of age, ringing with a new and fresh relevancy for contemporary readers.